2001
DOI: 10.1515/jbcpp.2001.12.2.125
|View full text |Cite
|
Sign up to set email alerts
|

Pitch Discrimination: Are Professional Musicians Better than Non-Musicians?

Abstract: Musicians are typically considered to exhibit exceptional auditory skills. Only few studies, however, have substantiated this in basic psychoacoustic tasks. The purpose of the present investigation was to expand our knowledge on basic auditory abilities of musicians compared to non-musicians. Specific goals were: (1) to compare frequency discrimination thresholds (difference limen for frequency [DLF]) of non-musical pure tones in controlled groups of professional musicians and non-musicians; (2) to relate DLF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
163
3
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(204 citation statements)
references
References 17 publications
36
163
3
2
Order By: Relevance
“…The reason for the diurnal variation of P300 latency occurring only under the high-frequency condition is unclear. It may be that subjects were more sensitive to the highfrequency stimuli than that to the low-frequency stimuli (Sek and Moore, 1995;Kishon-Rabin et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the diurnal variation of P300 latency occurring only under the high-frequency condition is unclear. It may be that subjects were more sensitive to the highfrequency stimuli than that to the low-frequency stimuli (Sek and Moore, 1995;Kishon-Rabin et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The participants were assigned to three groups that were matched for age and sex (see Table 1). The groups were also matched for number of participants who played a musical instrument, since professional musicians have lower pitch discrimination thresholds than nonmusicians (Kishon-Rabin, Amir, Vexler, & Zaltz, 2001). Because pitch discrimination is also correlated with IQ measures (Deary, 1994), we administered the Wechsler Abbreviated Scale of Intelligence (WASI; Psychological Corporation, 1999).…”
Section: Methods Participantsmentioning
confidence: 99%
“…Musicians had more right matches for isolate tones than non-musicians (Table 1). It is known that musicians have better frequency perception and discrimination than non--musicians (13)(14)(15)(16)(17) and the lack of musical exposure may be one of the causes for a possible pitch-matching inaccuracy (2) . During the task that involved the reproduction of a sound sequencing of frequency patterns, musicians also showed a better performance when compared to non-musicians (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that musical experience enhance auditory perception, both of duration and frequency, given that musicians are superior to non-musicians (18)(19)(20) . When comparing isolate tone tasks with tone sequencing, both groups had more right matches at the isolate tone task and, for the NMG, the sequencing task turned out to be more difficult ( Table 3), showing that it seems that musical learning, either formal or informal, helps the individual to overcome this greater difficulty that is the sound sequencing (13)(14)(15)(16)(17) . This fact corroborates the study that concluded that the longer the sequence of auditory stimuli for the sequencing task, the more difficult the activity becomes, since it involves a greater number of auditory abilities (12) and a greater auditory processing refinement (21) .…”
Section: Discussionmentioning
confidence: 99%